MORALS, JUSTICE AND POLITICAL PHILOSOPHY - Derda Küçükalp (Felsefe Dünyası)
İn this study, an evaluation on the relationship between morals and justice has been presented.This evaluation has been carried out on the basis of political philosophy. İn this regard, political philosophy manifests itself as a quest for the realization of a good common life. The equivalent in political philosophy of the realization of a goos common life is a just political order. Justice corresponds to the intersection of morals and politics. The interpretation of this intersection ; that is the understanding of justice differs according to the understandings of political philosophy. The dominant approach in modern political philosophy is liberal political philosophy. Liberal political philosophy puts forth an understanding of justice that is very weak (formal) in terms of its moral content. Liberal understanding of justice is problematic due to the fact that it is based on a weak relationaship between morals and politics. There is a need to reconsider classical political philosophy in order to eliminate this problem even if it is a partial elimination. There is a strong bond between morals and politics in classical political philosophy.Hence, classical political philosophy has a strong understanding of justice contrary to modern political philosophy.